Ethical decision-making regarding infant viability: A discussion. (November 2018) - Kelly, Janet; Welch, Emma
Background: There are no universally agreed rules of healthcare ethics. Ethical decisions and standards tend to be linked to professional codes of practice when dealing with complex issues. Objectives: This paper aims to explore the ethical complexities on who should decide to give infants born on the borderline of viability lifesaving treatment, parents or the healthcare professionals. Method: The paper is a discussion using the principles of ethics, professional codes of practice from the UK, Nursing Midwifery Council and UK legal case law and statute. Healthcare professionals' experiences that influence parental decision are also considered. Findings & Discussion: There are considerable barriers to an effective discussion taking place in an environment where clinical decisions have to be made quickly once the baby is born. This is compounded by the need and respect for parental autonomy and the difficulties they face when making a best interest's decision knowing that this could cause more harm than good for their infant child and balancing any decision they make with quality of life. Conclusion: On deciding whether to give lifesaving treatment born at the borderline of viability, it should be a joint decision between the parents and the neonatal team.